Prelamin A processing, accumulation and distribution in normal cells and laminopathy disorders. (1st March 2016) - Casasola, Andrea; Scalzo, David; Nandakumar, Vivek; Halow, Jessica; Recillas-Targa, Félix; Groudine, Mark; Rincón-Arano, Héctor
ABSTRACT: Lamin A is part of a complex structural meshwork located beneath the nuclear envelope and is involved in both structural support and the regulation of gene expression. Lamin A is initially expressed as prelamin A, which contains an extended carboxyl terminus that undergoes a series of post-translational modifications and subsequent cleavage by the endopeptidase ZMPSTE24 to generate lamin A. To facilitate investigations of the role of this cleavage in normal and disease states, we developed a monoclonal antibody (PL-1C7) that specifically recognizes prelamin A at the intact ZMPSTE24 cleavage site, ensuring prelamin A detection exclusively. Importantly, PL-1C7 can be used to determine prelamin A localization and accumulation in cells where lamin A is highly expressed without the use of exogenous fusion proteins. Our results show that unlike mature lamin A, prelamin A accumulates as discrete and localized foci at the nuclear periphery. Furthermore, whereas treatment with farnesylation inhibitors of cells overexpressing a GFP-prelamin A fusion protein results in the formation of large nucleoplasmic clumps, these aggregates are not observed upon similar treatment of cells expressing endogenous prelamin A or in cells lacking ZMPSTE24 expression and/or activity. Finally, we show that specific laminopathy-associated mutations exhibit both positive and negative effects on prelamin A accumulation, indicating that these mutations affect prelamin A processing efficiency in different manners.